Internalisasi Nilai-nilai Budi Pekerti Pada Anak - Munjin Munjin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
The value education plays an important role to form children’s attitude. But it will be fruitless if it is just taught to the children by speech methode. Some experts claim that the appearing of negative conducts performed by teenagers is caused by the failure of using methode in the education of value. Moral is something practiced in our life, and not just be memorized, because it belongs to affective domain. Therefore, our schools just allocate a little and limited time to internalize it. The result is that the education of value turns to cognitive domain. So, we can see that there are many students with good remark but they act bad deed. Internal ization is regaded as the best way to plant that value.